TOPICAL THERAPY AND COMPRESSION THERAPEUTIC THERAPY FOR HEALING VENOUS LEG ULCERS: CASE STUDY - Rubiyanto Warja (Poltekkes Kemenkes Bengkulu, 2023)
Chronic venous disease (CVD) are general problem from venous leg system have three categories venous disease: deep vein thrombosis, varicose veins 10% - 15% case and the leading chronic venous insufficiency (CVI) have a complication venous leg ulcers (VLUs) occur because of incompetence valve of vein. A chronic VLUs is stasis ulcers and stalled in a persistent inflammatory stages, occurs in the presence of venous disease. The annual US Payer burden for VLU is estimate at 14.9 billion C6 in CEAP Classification CVI are active ulcers often recurrent at 57%-70% in a year. CVI lead diminished quality of life and not productivity more than 150.000 new patient in USA yearly. Gold standard to manage of VLUs wound care management included hygiene and debridement continue to choosing appropriate topical dressing. Gold standard VLUs introduce compression therapeutic therapy need high pressure 40 mmhg. Method Case Study A man 71 y.o. complaint wound in right leg more than six month non healing wound comorbid obesity, hypertension, varicose vein and CVI. CEAP classification C6, Es, As, Pr. ABPI measure 0.9, TBI 0.91. Wound bed swabbing culture Staphylococcus aureus bacterial colonies. Choose topical dressing using TIME framework, topical ozone (O3) hyperbaric therapy for release bioburden & synthesis collagen support in proliferating wound healing phases. Healing wound VLUs in seven weeks. This cases effective and efficient using compression therapeutic therapy and topical therapy suitable with literature. Appropriate dressing selection case VLUs need skill set. Compression therapy have three principle called “3C”: comfort, continuous and consistence pressure. Compression therapeutic therapy as gold standard to support healing in venous leg ulcers management.